The Influence of Digital Experience and E-Wom on Purchase Decisions and Customer Satisfaction: a Case Study of Grand Taman Safari Indonesia, Pasuruan - Ratnasari, Maya; Survival; Wulandari, Wahju (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2025)
This study investigates the role of digital experience and electronic word of mouth (E-WOM) on purchase decisions and their implications for customer satisfaction among visitors to The Grand Taman Safari Indonesia, Prigen, Pasuruan. An explanatory quantitative approach was employed, with data collected from 99 respondents and analyzed using SmartPLS. The findings indicate that digital experience has a positive but insignificant effect on both purchase decisions and customer satisfaction. Similarly, E-WOM shows a positive but insignificant effect on customer satisfaction, while it significantly influences purchase decisions. Furthermore, purchase decisions have a significant and positive impact on customer satisfaction. Mediation analysis reveals that purchase decisions do not significantly mediate the relationship between digital experience and customer satisfaction, but they do significantly mediate the effect of E-WOM on customer satisfaction. These results highlight the importance of optimizing E-WOM strategies to enhance customer engagement and satisfaction in the tourism sector. This research contributes to the growing body of knowledge on digital marketing in tourism by emphasizing the mediating role of purchase decisions and providing practical insights for managing digital customer experiences.